On-Shelf Availability (OSA) and firm performance: the moderating effects of lean practices in retail industry - Halim Hamim; Norlena Hasnan; Maryam Jamilah Asha'ari (Penerbit Universiti Kebangsaan Malaysia, 2023)
This study addressed the problem of retailers struggling with store operations, which negatively affects customer satisfaction, sales, and overall firm performance. The objective was to investigate the relationship between on shelf availability and firm performance in Malaysian retail small and medium enterprises. The study examined the impact of operational and managerial factors as determinants of on-shelf availability, as well as the moderating effect of lean practice on these relationships. A survey was conducted among retail Small and Medium Enterprises owners in the central region of Peninsular Malaysia, resulting in 151 usable responses. Data analysis was performed using Partial Least Squares Structural Equation Modeling. The main findings revealed that operational factors had a significant positive effect on firm performance, whereas managerial factors did not show a significant effect. Furthermore, the study demonstrated that lean practice moderated the relationships between operational factors and firm performance, as well as between managerial factors and firm performance. These findings have significant practical implications for retail small and medium enterprises owners, researchers, and policymakers. Retail small and medium enterprises, should invest in efficient operational practices, incorporating lean practices cautiously, emphasizing bottleneck and constraint management to boost firm performance.